Pengaruh Suhu dan Lama Penyimpanan Terhadap Kadar Vitamin C pada Jus Jambu Biji (Psidium Guajava L.) - Hapsari, Yuliana Indra; Lestari, Yanesti Nur Avianda; Prameswari, Galuh Nita (Universitas Muhammadiyah Semarang, 2023)
Guava juice is one of the healthiest drinks and can be used as a healthy snack. However, people tend to wait for a certain period of time to consume juice. This can affect the levels of vitamin C in it. The purpose of this study was to identify the effect of temperature and storage time on vitamin C levels in guava juice (Psidium guajava L.). The research design was a factorial randomized block design (RAK) with a 2 x 3 pattern, which consisted of two factors, namely: The influence of storage temperaturewhich consisted of 2 levels, namely cold temperature (6.6 -10°C) and roomtemperature (28 -32 °C) and the storage time factor consisted of 3 levels, namely 30 minutes, 60 minutes, and 90 minutes so that the total treatment in this study amounted to 6 treatments. Analysis of vitamin C in this study used the UV-VIS spectrophotometry method. Each treatment will be repeated measurements of vitamin C levels 3 times. The data that has been obtained were analyzed using the Friedmann test with the MannWhitney advanced test (CI = 95%). The results showed that there was an interaction between the combination of temperature and storage time which significantly affected the decrease in vitamin C levels in guava juice (Psidium guajava L.). The lowest vitamin C content in guava juice (Psidium guajava L.) was found in the L2S2 treatment, namely storage at room temperature with a storage time of 60 minutes. In waiting for consumption, people should store fruit juice in the refrigerator so that the vitamins they get are more optimal.Keywords: Vitamin C, Fruit Juice, Guava, Temperature, Storage Time, Spectrophotometry.